QUATERNARY PREVENTION IN THE USE OF BLOOD PRODUCTS - MCKD Nascimento; CB Sousa (Hematology, Transfusion and Cell Therapy)
Background and objectives: Quaternary prevention refers to medical strategies aimed at preventing or mitigating unnecessary and iatrogenic interventions in health promotion. In the context of the use of blood products, quaternary prevention is essential to ensure safety and avoid the risks and potential complications associated with transfusions. In this sense, the use of these components must be carefully evaluated in order to avoid complications and obtain the expected clinical results. The aim of this study is to evaluate the implementation of quaternary prevention practices in the use of blood products, with a view to reducing the incidence of unnecessary transfusions and minimizing risks to patients. Material and methods: This study consists of a systematic literature review based on the PRISMA 2020 guideline, including a critical analysis. The keywords “quaternary prevention”, “blood transfusion” were used in the Coleciona SUS, Medline and LILACS databases, accessed through the Virtual Health Library. The selection of articles was restricted to the period 2014 to 2024, considering those written in Portuguese and English and directly related to the topic. Duplicate or non-pertinent articles were excluded. Results: A total of 96 articles were found in the search, and 10 pertinent to the theme were selected. Quaternary prevention in the use of blood products requires a rigorous assessment of the clinical need for transfusions, either through laboratory indicators, using well-defined and evidence-based criteria associated with the patient's clinical condition (such as volume loss of more than 25% to 30% of volemia, acute hemorrhages with clinical signs of poor tissue perfusion, Hb less than 7 g/dL or less than 9g/dL depending on comorbidities, thrombocytopenia < 10000 with hemorrhagic manifestations and others). In addition to possible hemolytic, febrile and allergic reactions and transmission of infections, the excess volume caused by blood component transfusions can cause circulatory overload, acute lung injury, shock, respiratory failure and death. Discussion: Hospital protocols for restrictive transfusion should be used, as it has been shown that more conservative approaches have similar efficacy and a lower risk of complications when compared to more liberal protocols. In addition, the use of alternatives to transfusion with the use of pharmacological agents such as erythropoietin and antifibrinolytics and minimally invasive surgical techniques to reduce blood loss are important to avoid the indiscriminate use of blood products. Conclusions: Quaternary prevention in the use of blood products is crucial to protect patients from unnecessary interventions and potential harm, especially those related to circulatory overload, shock and death.